2009
DOI: 10.1002/art.24261
|View full text |Cite
|
Sign up to set email alerts
|

HLA–E gene polymorphism associated with susceptibility to kawasaki disease and formation of coronary artery aneurysms

Abstract: Objective. Kawasaki disease (KD) is a pediatric systemic vasculitis of unknown cause for which a genetic influence is supposed. The purpose of this study was to identify possible genetic variants in the major histocompatibility complex (MHC) region that are associated with KD and the development of coronary artery aneurysms (CAAs) in a Taiwanese population.Methods. The 168 genetic variants covering the MHC locus were analyzed in an association study of a Taiwanese cohort of 93 KD patients and 680 unrelated hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 50 publications
2
61
0
Order By: Relevance
“…This observation has been confirmed by studies of surveillance in larger groups of patients with KS from Japan, Korea and Taiwan [17][18][19]. Possible genetic variants in the major histocompatibility complex region that are associated with KS might influence the responsiveness to IVIG and the development of CAA [20,21].…”
Section: Discussionmentioning
confidence: 82%
“…This observation has been confirmed by studies of surveillance in larger groups of patients with KS from Japan, Korea and Taiwan [17][18][19]. Possible genetic variants in the major histocompatibility complex region that are associated with KS might influence the responsiveness to IVIG and the development of CAA [20,21].…”
Section: Discussionmentioning
confidence: 82%
“…However, administration of IVIg reduces coronary artery abnormalities such as aneurisms from 20% to 25% to 3% to 5% within 10 days of illness onset. 43 Recently, Lin et al 44 highlighted the role of HLA-E in the pathogenesis of KD. They measured plasma concentrations of soluble HLA-E (sHLA-E) by enzyme-linked immunosorbent assay in 96 Taiwanese patients with KD and in 93 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have revealed inconsistent results (Table 1) [45][46][47][48][49][50][51][52][53][54][55][56][57] . These results indicate that the genes responsible for susceptibility and CAL formation may be different between populations [7,32,37,38,[58][59][60] . Recently, several candidate genes have been proposed for (Table 2).…”
Section: Introductionmentioning
confidence: 86%
“…For example, a number of genes have been reported to have significant associations with the susceptibility to KD in different populations. For instance, single nucleotide polymorphisms (SNPs) in the monocyte chemoattractant protein 1 (MCP-1) [29] , IL-10 [30][31][32] , CD40L [33] , IL-4 [26] , CASP3 [20,34] , IL-18 [35] , IL-1B [36] , HLA-E [37] , C-C chemokine receptor 5 (CCR5) [38] , and inositol 1, 4, 5-trisphosphate 3-kinase C (ITPKC) [21,39] have been reported to be associated with the development of KD. In early 2011, Shimizu et al [12] first reported that genetic polymorphisms of TGFB2, TGFBR2, and SMAD3 are associated with susceptibility to Kawasaki disease and the development of coronary artery lesions.…”
Section: Introductionmentioning
confidence: 99%